How to Identify Common Variable Immunodeficiency Patients Earlier: General Practice Patterns - Ilkjær, Frederik V.; Rasmussen, Line D.; Martin-Iguacel, Raquel; Westh, Lena; Katzenstein, Terese L.; Hansen, Ann-Brit E.; Nielsen, Thyge L.; Larsen, Carsten S.; Johansen, Isik S. (Journal of clinical immunology, 2019)
Purpose Diagnostic delay is a major problem concerning common variable immunodeficiency (CVID). We aimed to determine the pattern of general practitioner (GP) consultations in individuals diagnosed with CVID within 3 years before the diagnosis and whether the risk of diagnosis was associated with the frequency of consultations or character of examinations. Methods We conducted a nested case-control study, identifying 132 adult CVID patients and 5940 age- and gender-matched controls from national registers during 1997–2013. We used conditional logistic regression to calculate the odds ratios (OR) and 95% confidence intervals (95%CI). Results The median number of consultations among individuals with CVID was more than twice that of the controls in all 3 years (3rd, 10; 2nd, 11.5; and 1st, 15.4 vs. 4). We found a statistically significant association between the number of consultations and the risk of a subsequent CVID diagnosis, independent of age and gender, but strongest in the individuals < 40 years. In the 3rd year before diagnosis, having 9–15 consultations compared with 1–4 was associated with an OR (95%CI) of 5.0 (2.3–10.9), 2.4 (1.1–5.4), and 1.3 (0.3–5.3) for those aged 18–40, 41–60, and > 60, respectively. Several examinations (i.e., blood tests for inflammation/infection and pulmonary function test) were associated with increased odds of a subsequent CVID diagnosis. Conclusion The risk of a CVID diagnosis was highly related to both the number of consultations and the character of examinations performed by the GP. CVID should be a differential diagnosis among patients with multiple consultations, especially in patients < 40 years old.